Efforts to Improve the Quality of Public Services in the Education Sector - Anita Zuli Rahmawati (DIMAR: Jurnal Pendidikan Islam, 2021)
Public service is a product of public bureaucracy that is accepted by users and the wider community. Therefore, public service can be defined as a series of activities carried out by the public bureaucracy, for example making identity cards, birth certificates and so on. Improvements to public services, especially in education, will improve and be more equitable. This is due to many limitations, both in terms of education budget, teaching staff, facilities such as school buildings, libraries, laboratories and scholarships for the poor. Therefore, it is hoped that educational services can be felt equally by the community in meeting their basic needs. In carrying out innovations in the field of education, the Regency Government directs, guides, supervises, supervises, coordinates, monitors, evaluates, and controls the organizers of units, pathways, levels, and types of education in accordance with national policies in the field of education and regional policies in the field of education within the framework of managing the education system. National Analysis of the challenges faced and opportunities for service development of the Kediri District Education Office requires an analysis of internal and external conditions. This requires an analysis of the strengths, weaknesses, opportunities, challenges (Threats), or a SWOT analysis of the conditions of education, youth and sports in Kediri Regency which is basically a description of the service performance of the Kediri Regency Education Office.